La Química y los Cosméticos - Aguirre, J. Dafhne (Pontificia Universidad Católica del Perú, 2022)
At first glance it may seem strange to connect chemistry with cosmetics. Nothing further from the truth since both are a constant in our daily lives. The average person uses at least 5 cosmetic products daily, which translates into at least 150 different chemical compounds being applied into our bodies every day. Unfortunately, an increase in misinformation has led to an ever-growing fear of chemical compounds. Consequences of the misrepresentation of chemicals, good and bad, have plagued the cosmetics industry. One of the most affected compounds by misinformation are parabens, which are commonly used as preservatives in cosmetic products. The consensus of both scientific and dermatological community is that parabens are not only risk-free, but also highly beneficial to stop contamination with fungi and other microorganisms. Currently, parabens are considered some of the least allergenic preservatives available, with rates of contact sensitization between 0.5% to 1.4%. Nevertheless, consumers and clean beauty movement supporters have it classified as a high-risk product that should be completely banned. On one hand, by not using parabens, products risk being contaminated, on the other hand laboratories are now trying to find other alternatives to these compounds. Being well informed about the ingredients of a product is the consumers’ right of, and an obligation of the industry, but it does not relieve the public to its responsibility to be well-informed. At the same time, the responsibility of the scientific community is to try to inform the public using simpler terms and making science accessible to everyone.

Aunque a primera vista cause extrañeza conectar la química con la cosmética, en realidad, ambos temas están presentes constantemente en nuestra vida diaria. No hay persona que no utilice por lo menos cinco productos cosméticos cada día, lo que se traduciría en utilizar diariamente, por lo menos, 150 diferentes compuestos químicos. Lamentablemente, el aumento de desinformación ha ocasionado un temor por los compuestos químicos lo cual ha traído consecuencias, buenas y malas, a la industria de los cosméticos. Uno de los compuestos que han sido más afectados por la desinformación son los parabenos, comúnmente utilizados como preservantes en productos cosméticos. En este caso hay dos visiones opuestas: mientras que la industria dermatológica y la comunidad científica acepta los parabenos como los productos conservantes menos alergénicos actualmente disponibles, con tasas de sensibilización al contacto entre 0,5% a 1,4% y altamente beneficiosos para detener la contaminación con hongos y otros microorganismos, el público en general y los partidarios del movimiento de belleza limpia los tienen clasificados como productos de alto riesgo que deberían ser completamente prohibidos. Por una parte, no usar parabenos trae como consecuencia altas probabilidades de contaminación del producto, la buena noticia es que laboratorios están tratando de encontrar otras alternativas a estos compuestos. Estar bien informados del contenido de un producto es un derecho del público (y una obligación de la industria), pero no exime a este último de su responsabilidad de informarse. Al mismo tiempo, la comunidad científica tiene la responsabilidad de tratar de informar usando términos más sencillos y haciendo que la ciencia esté al alcance de todos.
Chemistry and Cosmetics
Keywords: Química; https://purl.org/pe-repo/ocde/ford#1.04.00